Graphic signs of identity, faith, and power in Late Antiquity and the Early Middle Ages - Garipzanov, Ildar; Goodson, Caroline; Maguire, Henry (Cursor mundi, 2017)
Brings together historians, art historians, and archaeologists to discuss the role of graphic representational signs and symbols and to look at contexts facilitating their dissemination in a wide range of media in the late Roman and post-Roman worlds. 0In this volume, twelve specialists examine the role of graphic signs such as cross signs, christograms, and monograms in the late Roman and post-Roman worlds and the contexts that facilitated their dissemination in diverse media. The essays collected here explore the rise and spread of graphic signs in relation to socio-cultural transformations during Late Antiquity and the early Middle Ages, focusing in particular on evolving perceptions and projections of authority. They ask whether some culturally specific norms and practices of graphic composition and communication can be discerned behind the rising corpus of graphic signs from the fourth to tenth centuries and whether common features can be found in their production and use across various media and contexts. The contributors to this book analyse the uses of graphic signs in quotidian objects, imperial architectural programmes, and a wide range of other media. In doing so, they argue that late antique and early medieval graphic signs were efficacious means to communicate with both the supernatural and earthly worlds, as well as to disseminate visual messages regarding religious identity and faith, and social power